CLINICAL AND PLASMA PROTEOMIC MARKERS CORRELATING WITH CHRONIC KIDNEY DISEASE AFTER LIVER TRANSPLANTATION - Levitsky, Josh (2011)
Chronic kidney disease (CKD) occurs frequently after liver transplantation (LT) and is associated with significant morbidity and mortality. Thus, there is a pressing need to identify characteristics and biomarkers diagnostic of CKD to enable early diagnosis allowing preemptive interventions, as well as mechanistic insights into the progression from kidney injury to irreversible kidney failure. We analyzed 342 patients who had baseline GFR>60 at time of LT and are now >3 years post-LT. Risk factors for post-LT CKD were compared between 3 different groups defined by current GFR: >90 (n=40), 60–90 (n=146) and <60 (n=156) ml/min. Age, cyclosporine use, and pre-LT GFR were independently associated with new onset CKD. A subset (n=64) without viral/immune disease or graft dysfunction underwent multi-analyte plasma proteomic evaluations for correlation with CKD. Plasma proteomic analysis of two independent cohorts, test (n=22) and validation (n=42), identified 10 proteins highly associated with new onset CKD. In conclusion, we have identified clinical characteristics and a unique plasma proteomic signature correlating with new onset CKD after LT. These preliminary results are currently being validated in a prospective, multi-center study to determine if this signature precedes the onset of CKD and resolves with early interventions aimed at preserving kidney function.